Remote sensing based strategy of stream sediment sampling for mineral exploration in Peshawar Basin, Khyber Pakhtunkhwa, Pakistan - Shafique, Mohammad; Israr, Sarmad; Shah, Mohammad Tahir; Khan, Mohammad Asif (Journal of Himalayan Earth Sciences, 2014)
Remote Sensing (RS) and Geographic Information System (GIS) are frequently and effectively used in exploration and sustainable utilization of mineral resources. Minerals of economic importance can play a significant role in the socio-economic development of the society. The initial step in mineral exploration at a regional scale is the stream sediments survey to locate the prospecting areas. The presence of heavy minerals and metals in stream sediments is used as an indicator for the existence of source rock in the watershed of the corresponding stream. The province of Khyber Pakhtunkhwa in Pakistan is blessed with minerals of economic importance. However, there is a need for their exploration and sustainable utilization. In the present study RS and GIS techniques are used to assist in exploring the mineral resources in the Peshawar basin of the Khyber Pakhtunkhwa which mainly comprises of five districts. The freely available remote sensing based Digital Elevation Model (DEM) is used for hydrological modelling to map the streams network in the basin and their corresponding watersheds. The watershed outlets of the first order streams are mapped and are proposed as the optimal sites for collection of stream sediments samples for subsequent mineralogical and geochemical analysis. The geochemical analyses of stream sediments can be used to demarcate watersheds with potential minerals concentrations. The proposed methodology can be effectively replicated in any minerals prospecting area.